2017
DOI: 10.1002/acr.23143
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Clinical Factors Associated With Low Disease Activity and Remission of Rheumatoid Arthritis During Pregnancy

Abstract: Objective. To identify a combination of clinical factors associated with low disease activity and remission in the third trimester during pregnancy in women with rheumatoid arthritis (RA).Methods. This study is embedded in the Pregnancy-Induced Amelioration of Rheumatoid Arthritis study, a prospective cohort study. There were data available on 190 pregnancies from first trimester until delivery. Multivariate regression analyses were performed on the disease activity (Disease Activity Score in 28 joints [DAS28]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…However, the fact that the time TNFi were stopped in that study was on average earlier in gestation compared to the women in our sample indicates that the timing of drug discontinuation during pregnancy may be of importance. Moreover, the authors also showed an association of flares during pregnancy with elevated disease activity in early pregnancy, a finding that was confirmed by others (). In contrast, studies of nonpregnant patients with RA have demonstrated that low disease activity at the time of TNFi discontinuation is a predictor of maintained benefit .…”
Section: Discussionsupporting
confidence: 74%
“…However, the fact that the time TNFi were stopped in that study was on average earlier in gestation compared to the women in our sample indicates that the timing of drug discontinuation during pregnancy may be of importance. Moreover, the authors also showed an association of flares during pregnancy with elevated disease activity in early pregnancy, a finding that was confirmed by others (). In contrast, studies of nonpregnant patients with RA have demonstrated that low disease activity at the time of TNFi discontinuation is a predictor of maintained benefit .…”
Section: Discussionsupporting
confidence: 74%
“…This study is embedded in the Pregnancy-induced Amelioration of Rheumatoid Arthritis (PARA) study, a prospective cohort study on pregnancy and RA 29. From 2002 to 2008, 369 female patients with RA who had a wish to conceive (or already pregnant) were enrolled 30 31. After participation in the PARA study, 196 children and their parents were invited to participate in a follow-up study, the FEtal Programming in Rheumatoid Arthritis (FEPRA) study.…”
Section: Methodsmentioning
confidence: 99%
“…In the PARA study, data on mother (eg, disease activity (with the Disease Activity Score in 28 joints using C reactive protein levels, DAS28-CRP 3 )) and child were collected 31. For the FEPRA study, data on blood pressure, growth and body composition of the children were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, there is no clear predictor of remission, other than seronegative status [24]. Other studies have suggested that disease activity pre-conception or in early pregnancy can predict flare during pregnancy [25,26]. Although there does not appear to be an increased risk for congenital malformations as a result of RA itself, the presence of RA itself can influence the course of pregnancy.…”
Section: Ra and Pregnancymentioning
confidence: 99%